'Little people do little things': the motivation and recruitment of Viet Cong child soldiers. Issue 1 (2nd January 2022) - Nguyen, Mai Anh
ABSTRACT: Children have comprised a significant part of past and present military conflicts; however, attempts to understand their motivations have generally focused on coerced recruitment. When children join military groups without physical coercion, they are portrayed as being driven by economic and social deprivations. This article investigates factors that have been disproportionately overlooked as motivators for child soldiers – social contexts, relationships, and personal histories. To this end, I use a relational approach to analyse life histories of former Viet Cong child soldiers. I explore their lives prior to joining the Viet Cong guerrillas and trace how their choice to do so had been shaped by societal factors including family, perceptions of a good childhood, and previous war exposure. My interviews further indicate that children actively reproduced and appropriated the same practices that predisposed them to take up arms. Evaluated against the backdrop of their social and internal lives, the decision of child soldiers to participate in the Vietnam War is understood to be a product of their personal and social histories. These findings challenge the stereotypical image of the passive child soldier. Such historisation of children's recruitment helps to destigmatise child soldiers' experience and allow for a more nuanced understanding of their decisions.